Possibility of a risk‐adapted treatment strategy for untreated aggressive adult T‐cell leukaemia‐lymphoma (ATL) based on the ATL prognostic index: a supplementary analysis of the JCOG9801. (16th May 2019) - Toyoda, Kosuke; Tsukasaki, Kunihiro; Machida, Ryunosuke; Kadota, Tomohiro; Fukushima, Takuya; Ishitsuka, Kenji; Maruyama, Dai; Nagai, Hirokazu
Summary: JCOG9801, a randomized phase III trial, reported that vincristine, cyclophosphamide, doxorubicin and prednisone (VCAP); doxorubicin, ranimustine and prednisone (AMP); and vindesine, etoposide, carboplatin and prednisone (VECP) (VCAP‐AMP‐VECP; mLSG15) showed superior clinical outcomes when compared to cyclophosphamide, doxorubicin, vincristine and prednisone every 2 weeks (CHOP‐14; mLSG19) in patients with untreated aggressive adult T‐cell leukaemia‐lymphoma (ATL). To identify patients who require VCAP‐AMP‐VECP, we conducted a supplementary analysis of JCOG9801. Overall, 105 patients were included and categorized into low‐ ( n  = 44), intermediate‐ ( n  = 54) and high‐risk ( n  = 7) groups according to the age‐adjusted ATL prognostic index (ATL‐PI). We excluded the high‐risk group due to small numbers of patients. VCAP‐AMP‐VECP did not show any superior trend for overall survival (OS) in the low‐risk group (hazard ratio: 1·04; 95% confidence interval: 0·54–2·04). Better OS was observed in the intermediate‐risk group treated with VCAP‐AMP‐VECP (hazard ratio: 0·65; 95% confidence interval: 0·36–1·19). In the intermediate‐risk group, the VCAP‐AMP‐VECP arm showed higher complete response rates than the CHOP‐14 arm (44·0% vs. 13·8%). The VCAP‐AMP‐VECP arm in both risk groups exhibited grade 4 thrombocytopenia, while grade 4 neutropenia was only observed in the intermediate‐risk group. VCAP‐AMP‐VECP remains suitable for the intermediate‐risk group, whereas its benefits appear modest in the low‐risk group.